ECONOMIC VALUE ADDED, MARKET VALUE ADDED, DAN KINERJA KEUANGAN TERHADAP RETURN SAHAM - RUTJI SATWIKO; VLADIMIR AGUSTO (Media Bisnis, 2021)
The research objective is to determine the variables that affect stock returns. The independent variables used in this study are economic value added, market value added, debt to equity ratio, price to book value, total assets turnover, return on equity, net profit margin, and earnings per share. The dependent variable in this study is stock returns. The population in this study were non-financial companies listed on the Indonesia Stock Exchange for 5 consecutive years, from 2013 to 2017. The sample selection method used was purposive sampling. The research sample is 52 non-financial companies listed on the Indonesia Stock Exchange. Hypothesis testing uses multiple regression models. The results indicate that economic value added, debt to equity ratio, total assets turnover, net profit margin, and earnings per share have no effect on stock returns. However, market value added and return on equity have a positive effect on stock returns. Meanwhile, price to book value has a negative effect on stock returns.